2021
DOI: 10.3389/fendo.2021.642698
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms in Lysyl Oxidase Family Genes Are Associated With Intracranial Aneurysm Susceptibility in a Chinese Population

Abstract: PurposeIntracranial aneurysms (IA) comprise a multifactorial disease with unclear physiological mechanisms. The lysyl oxidase (LOX) family genes (LOX, LOX–like 1–4) plays important roles in extracellular matrix (ECM) reconstruction and has been investigated in terms of susceptibility to IA in a few populations. We aimed to determine whether polymorphisms in LOX family genes are associated with susceptibility to IA in a Chinese population.MethodsThis case-control study included 384 patients with IA and 384 heal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 46 publications
(63 reference statements)
2
3
1
Order By: Relevance
“…Our present study demonstrated that LOXL1 rs2165241 was associated with multiple IAs ruptures. This is different from our previous study, which did not find an association between LOXL1 and IAs susceptibility ( 14 ). This may be due to the fact that the pathobiology leading to IAs formation and its rupture are not exactly the same, causing the existing IA rupture (aSAH) is a separate process from an IA formation ( 12 ).…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…Our present study demonstrated that LOXL1 rs2165241 was associated with multiple IAs ruptures. This is different from our previous study, which did not find an association between LOXL1 and IAs susceptibility ( 14 ). This may be due to the fact that the pathobiology leading to IAs formation and its rupture are not exactly the same, causing the existing IA rupture (aSAH) is a separate process from an IA formation ( 12 ).…”
Section: Discussioncontrasting
confidence: 99%
“…In the present study, significant associations between LOX (rs1800449 and rs10519694) and single IA rupture were detected. Similar to our previous study, it was found that LOX was associated with IA susceptibility (14), but these results are inconsistent with those of a previous study by Hong et al, who conducted a case-control study with 41 ruptured and 39 unruptured IA patients in a Korean population and showed that LOX may not be a susceptibility gene for IA rupture (17). We found that population heterogeneity may be the reason for the discordance between these 2 countries, and minor allele frequency in the 2 sites was discrepant between these 2 populations.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Epidemiological investigations showed that rst-degree relatives of IA patients had 7 times higher risk for the disease than the general population [8]. Some large-sample case-control studies found that genetic variants of LOX, ANGPTL6, FBLN2, NOTCH3, PCNT, ARHGEF17 genes were associated with higher risks for IAs [9,10].…”
Section: Introductionmentioning
confidence: 99%